The effectiveness of palm oil fuel ash cement paste to control degradation in ammonium nitrate solution - Tasnim, Sadia; M. E, Rahman; A, Raudhah; Doh, Shu Ing (IOP Publishing, 2020)
This paper presents the use of treated palm oil fuel ash (POFA) as a pozzolanic material in modified cement paste to control degradation in ammonium nitrate environment. The POFA used in this study had a mean diameter of 8.7μm. The treated POFA was used to replace cement in different percentage of 0%, 10%, 20% and 30% with a constant water to cement ratio of 0.4. 50mm cement cubes was prepared for mechanical, durability and micro-structural test. Mechanical test consisted of the compression strength test and durability test consisted of the Volume of Permeable Voids Test (VPV). Meanwhile, micro-structural test consisted of the Thermo-gravimetric analysis (TGA). After 28 days of full water curing, the 50mm cubes samples were immersed in 20% ammonium nitrate solution until 90 days. Based on the test results, it was observed that, cement cubes replaced with 20% POFA had good resistance against ammonium nitrate solution. However, in order to improve the current study, a number of recommendations had been suggested.